Mapping the Knowledge Landscape of Local and Traditional Ecological Knowledge (LEK/TEK) in Mangrove Ecosystems: A Bibliometric Analysis in the Past Decade - Sunarto, Sunarto; Mamangkey, Jendri (Publisher Cv. Inara, 2025)
Local Ecological Knowledge (LEK) and Traditional Ecological Knowledge (TEK) play a crucial role in mangrove ecosystem management, restoration, and community livelihoods. Over the past decade, scholarly interest in this topic has grown, yet research remains scattered across regions and disciplines. This study employed a bibliometric analysis of Scopus-indexed publications from 2014–2024, focusing on LEK/TEK in mangrove ecosystems. A total of 93 open-access articles and conference papers were identified. Results show two major research clusters: (i) ecosystem restoration, conservation, and ecosystem services, and (ii) ethnobotany and medicinal applications of mangrove species. Global publication patterns highlight Indonesia, India, and Bangladesh as leading contributors, while citation impact is distributed across both ecological and ethnobotanical studies. Despite growing attention, gaps remain in cross-regional comparisons, integration of LEK/TEK into policy, and interdisciplinary approaches bridging ecological, cultural, and governance perspectives. The findings provide a comprehensive overview of global scholarship and highlight future directions to strengthen the role of LEK/TEK in sustaining mangrove ecosystems.